A method of solving y(k)−f(x)y=0 - P. J. O'Hara; R. Osteen; R. S. Rodriguez (International Journal of Mathematics and Mathematical Sciences)
An alternative method is shown for solving the differential equation y(k)−f(x)y=0 by means of series. Also included is a result for a sequence of functions {Sn(x)}n=1∞ which gives conditions under which limn(dkdxkSn(x))=dkdxk(limnSn(x)).